Inklusi Keuangan dan Pemberdayaan Ekonomi: Evaluasi Efektivitas Produk Keuangan Syariah dalam Meningkatkan Akses Keuangan bagi Masyarakat Marginal - Fitriani; Efendi Sugianto; Shylvia Andriani; Rihfenti Ernayani; Dyah Mieta Setyawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Financial inclusion and economic empowerment have become major focal points in efforts to improve financial access for marginalized communities. This is particularly crucial in the current global context where economic inequality and access to financial services remain serious issues. This article aims to evaluate the role of Shariah-compliant financial products in supporting financial inclusion and economic empowerment among marginalized groups. The literature review method used in this article provides a strong foundation for collecting and analyzing various related articles, including policy reviews and market analyses. Through in-depth review, this article illustrates that Shariah-compliant financial products have significant potential to provide more inclusive, transparent, and sustainable solutions in enhancing financial access for marginalized communities. Key factors such as trust, understanding of Shariah principles, and supportive regulations are also emphasized as essential elements in strengthening the effectiveness of these financial products. Additionally, the implications of the findings in this article are crucial in providing guidance for stakeholders, regulators, and financial practitioners. By understanding the potential and advantages of Shariah-compliant financial products, stakeholders can develop more effective strategies to improve financial inclusion and economic empowerment among marginalized communities. Thus, this article not only provides insights but also offers a clear direction for further steps in strengthening financial access for all layers of society, while promoting sustainable and inclusive economic development.